An Approach to the Design of Ducted Propeller - Celik, F.; Guner, M.; Ekinci, S. (SHARIF UNIV TECH, 2010)
This paper describes a design methodology for ducted propellers operating in a non-uniform wake field. An improved lifting line model is used to represent propeller blades where more realistic slipstream deformation behind the propeller is considered, while the duct and hub are modeled by ring vortex distributions. Duct and hub geometries are assumed to be known and their effects on the propeller are calculated during propeller design stage. At the same time, mutual interaction between duct/hub geometry and propeller is taken into consideration based on an iterative procedure. For numerical application of the present method, a design example is carried out and the effect of slipstream deformation is investigated in detail. Another application based on experimental work is also taken into account to present the accuracy of the calculated results by present method and Computational Fluid Dynamics (CFD) code. Finally, propulsive characteristics of ducted propellers obtained from present method are compared to those of CFD code and experimental results.
Keywords: Ducted propeller; Lifting line method; Surface vorticity method; CFD; Slipstream deformation; MODEL; Engineering